Réponses

  • carys
  • Modératrice confirmée
2013-03-09T16:28:12+01:00

1)

D = (12x + 3) (2x - 7) - 5x(2x - 7)

D = 24x² - 84x + 6x - 21 - 10x² + 35x

D = 14x² -43x - 21

D = (2x-7)(7x+3)

 

(2x-7)(7x+3) = 0

2x-7 = 0 OU 7x+3 = 0 

2x = 7     OU 7x = -3

x = 7/2    OU x = -3/7

 

voilà :) 

2013-03-09T16:37:17+01:00
D= (12x+3)(2x-7)-5x(2x-7)
= 24x^2 -84x +6x -21 -10x^2 +35x
= 14x^2 -43x -21

2) D= (12x+3)(2x-7)-5x(2x-7)
= (2x-7) [(12x+3) - 5x]
= (2x-7)(12x +3 -5x)
= (2x-7)(7x+3)

3) D = 0
(2x-7)(7x+3) = 0
2x-7 = 0 ou 7x+3 = 0
2x = 7 ou 7x = -3
x = 7/2 ou x = -3/7
= 3,5